2014
DOI: 10.1177/875687051403300405
|View full text |Cite
|
Sign up to set email alerts
|

School Counselors Training Paraprofessionals: A Practical Model for Providing Technical Assistance in the Rural School Setting

Abstract: The roles and responsibilities of school counselors who serve in rural settings have increased dramatically over the years. One new aspect of the school counselor's role is to provide inservice/preservice training for teachers and school staff. With the increasing numbers of paraprofessionals now working in the schools, there is a need to provide them with training in critical teaching functions. In this paper, we propose a model for providing technical assistance on teaching and classroom management to parapr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Rural school counselors, in a study by Monteiro-Leitner et al (2006), indicated that they often performed duties related to special education services and testing, for which they were neither prepared nor trained. Spending time on these other duties is likely due to a lack of personnel resources (Darch et al, 2014). School counselors in rural communities also may be called upon to serve as community mental health counselors, further expanding their role and engendering more confusion around the school counselor identity (Bardhoshi & Duncan, 2009; Hann-Morrison, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rural school counselors, in a study by Monteiro-Leitner et al (2006), indicated that they often performed duties related to special education services and testing, for which they were neither prepared nor trained. Spending time on these other duties is likely due to a lack of personnel resources (Darch et al, 2014). School counselors in rural communities also may be called upon to serve as community mental health counselors, further expanding their role and engendering more confusion around the school counselor identity (Bardhoshi & Duncan, 2009; Hann-Morrison, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%